COMPOSITION AND STYLISTIC USE OF RELATIONAL VERBS IN WORDS WITH THE ROOT -HOUSE- IN THE WORKS OF 1950–1960 BY F. A. VIGDOROVA (Proceedings of Southern Federal University. Philology, 2023)
DOI 10.18522/1995-0640-2023-3-20-29The purpose of the study is to determine the role of relational verbs in words with the root -house- in the works of 1950–1960 by F. A. Vigdorova. The article analyzes relational verbs with words with a root -house- in literary texts of 1950-1960 by F. A. Vigdorova, characterizing an important fragment of the picture of the world “House” for the writer. It has been established that relational verbs with words with the root -house- are used in texts to indicate the relationship of characters in the interpersonal and social spheres, to the ways of their manifestation, express the pragmatic, pedagogical views of the writer. In the works, as well as in the usage, these verbs are presented to a lesser extent (14) compared to actional ones (83), but they are stylistically significant in the mental-lingual complex of F. A. Vigdorova’s linguistic personality.The scientific novelty of the study lies in the fact that for the first time the analysis of the semantics of relational verbs with words with the root -house- in the prose of 1950–1960 was carried out. F. A. Vigdorova, which made it possible to expand the idea of the specifics of the writer’s idiostyle, which consists in describing the spiritual, social life of the country in 1920–1950, in particular, by examining the lexical-semantic groups of verbs with the semantics of 'relationship': verbs of social relations, verbs of interpersonal relations, verbs of possession, verbs of relationship, including those used in a figurative sense. The results of the work make a significant contribution to the developed methodology for the linguistic analysis of the Vigdorova’s text.Key words: predicate; relational verbs; idiostyle; mental-linguistic complex; lexico-semantic groups; semantics; words with the root -house-; the language of works by F. A. Vigdorova